2022
DOI: 10.3390/v14071491
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the SARS-CoV-2 Antibody Avidity Response Following Infection and Vaccination

Abstract: Serological assays capable of measuring antibody responses induced by previous infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been critical tools in the response to the COVID-19 pandemic. In this study, we use bead-based multiplex assays to measure IgG and IgA antibodies and IgG avidity to five SARS-CoV-2 antigens (Spike (S), receptor-binding domain (RBD), Nucleocapsid (N), S subunit 2, and Membrane-Envelope fusion (ME)). These assays were performed in several cohorts of healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
3
11
0
Order By: Relevance
“…Vaccine‐induced antibody levels wane over time, but earlier studies 28–30 assessed a relatively short window—generally up to 4 months postvaccination. Since then, additional research 31–37 confirmed that antibody titers continue to decrease up to 12 months after SARS‐CoV‐2 vaccination and observed reduced neutralization activity to emerging variants including Delta and Omicron. Although antibody levels in this study were measured at only one time‐point, results are consistent with this prior research, 31–34 as unboosted individuals for whom more time had passed between receipt of their primary vaccine and serologic testing (≥7 months) tended to have lower antibody levels than those vaccinated within 4 months of testing.…”
Section: Discussionmentioning
confidence: 91%
“…Vaccine‐induced antibody levels wane over time, but earlier studies 28–30 assessed a relatively short window—generally up to 4 months postvaccination. Since then, additional research 31–37 confirmed that antibody titers continue to decrease up to 12 months after SARS‐CoV‐2 vaccination and observed reduced neutralization activity to emerging variants including Delta and Omicron. Although antibody levels in this study were measured at only one time‐point, results are consistent with this prior research, 31–34 as unboosted individuals for whom more time had passed between receipt of their primary vaccine and serologic testing (≥7 months) tended to have lower antibody levels than those vaccinated within 4 months of testing.…”
Section: Discussionmentioning
confidence: 91%
“…Vaccine-induced antibody levels wane over time, but earlier studies [28][29][30] assessed a relatively short window-generally up to 4 months post-vaccination. Since then, additional research [31][32][33][34] confirmed that antibody titers continue to decrease up to 6 months after SARS-CoV-2 vaccination and observed reduced neutralization activity to emerging variants including Delta and Omicron. Consistent with this prior research, the analyses in this study demonstrate that in a cohort of vaccinated individuals, titers decrease over time, as individuals who were vaccinated at least seven months prior to serologic testing tended to have substantially lower titers than those vaccinated within four months of testing.…”
Section: Discussionmentioning
confidence: 93%
“…Antibody avidity refers to the binding strength to the target antigen and is a crucial feature of functionality. Although both binding and neutralizing antibodies have been described to wane over time (13)(14)(15)(16)(17)(18)(19), avidity has been shown to increase with the duration after contact through B cell maturation at germinal centers (14)(15)(16), thereby possibly offsetting the waning effect to an extent.…”
Section: Introductionmentioning
confidence: 99%